Immune inflammation and metabolic interactions in the pathogenesis of diabetic nephropathy - Guangjian Hou; Youzi Dong; Yuehua Jiang; Wenbo Zhao; Le Zhou; Shengnan Cao; Wei Li (Frontiers in Endocrinology)
Diabetic nephropathy (DN) is a significant microvascular complication of diabetes, substantially contributing to the global prevalence of end-stage renal disease. The pathogenesis of DN is multifactorial, involving both immune-inflammatory responses and metabolic dysregulation. Hyperglycemia, a hallmark of diabetes, initiates kidney damage through various mechanisms, including oxidative stress, the accumulation of advanced glycation end products (AGEs), and changes in renal blood flow. These processes lead to the hallmark pathological features of DN, such as glomerulosclerosis and tubulointerstitial fibrosis. The immune system, particularly macrophages, T cells, and B cells, plays a crucial role in the progression of kidney injury, with inflammatory cytokines such as TNF-α and IL-6 promoting renal inflammation and fibrosis. In addition, metabolic disturbances, notably insulin resistance and dysfunction in insulin signaling, contribute to kidney dysfunction through several key signaling pathways, including PI3K/Akt, mTOR, Wnt/β-catenin, JAK/STAT, and NF-κB. The interplay between immune responses and metabolic signaling exacerbates kidney damage, creating a feedback loop that accelerates the progression of DN. While current therapeutic strategies mainly focus on managing blood glucose levels and inflammation, emerging treatments, such as GLP-1 receptor agonists and SGLT2 inhibitors, show promise in addressing both the metabolic and inflammatory aspects of the disease. Future research should focus on unraveling the complex interactions between immune and metabolic pathways to develop more targeted and personalized treatments for DN. This review highlights the significance of these mechanisms in the pathophysiology of DN and calls for innovative therapeutic approaches to combat this debilitating condition.